Nanotechnology in Metformin Delivery: Fasting Blood Glucose and Neutrophil-Lymphocyte Ratio of Diabetic Rat Model - David Pakaya; Laurents Christovel Iban Demen; Haerani Harun; Sarifuddin Anwar; Gabriella Bamba Ratih Lintin (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Diabetes Mellitus (DM) is a chronic inflammatory disease characterized by hyperglycemia and increasing the neutrophil-lymphocyte ratio (NLR). Metformin has been widely used to treat hyperglycemia. Metformin nanoparticles can improve bioavailability and may reduce inflammation. This study aims to analyze the effectiveness of metformin nanoparticles delivery through fasting blood glucose (FGB) level and NLR in the diabetic rat model. This study used 16 white male Wistar rats, 8 weeks of age, and body weight (BW) 250-350 grams. The streptozotocin (STZ) 40 mg/kg BW were injected i.p. Rats were divided into 4 groups; K1: normal control; K2: negative control (diabetes model); K3: diabetes model treated with metformin 100mg/Kg BW; K4: diabetes model treated with nanoparticle metformin 100mg/kg BW. Blood analysis tests were conducted using the Pentra hematology analyzer. Data were analyzed using the Graphpad Prism program with the nonparametric Kruskal Wallis test. The K3 group showed a periodical decrease in FBG level from day 7 to day 28 by 122 ± 11.31 mg/dL, and the mean NLR value was 0.48 ± 0.3 x 103/uL. Group of K4 periodically decreased in FBG level, indicating that it was closer to normal than K3. The result showed that at day 28.79 ± 15.39 mg/dL, the mean NLR value slightly increased compared to the K3 group by 0.54 ± 0.3 x103/uL. The statistical tests showed a significant difference between the level of FBG (p 0.0089) but no significant difference in NLR (p 0.347). Metformin nanoparticles could decrease FBG levels and effectively reduce the NLR in the diabetic rat model.